Investigating the Binding Heterogeneity of Trace Metal Cations With SiO2 Nanoparticles Using Full Wave Analysis of Stripping Chronopotentiometry at Scanned Deposition Potential - Rotureau, Elise; Rocha, Luciana S.; Goveia, Danielle; Alves, Nuno G.; Pinheiro, José Paulo (Frontiers in Chemistry, 2020)
Silica oxides nano and microparticles, as well as silica-based materials are very abundant in nature and industrial processes. Trace metal cation binding with these bulk materials is generally not considered significant in speciation studies in environmental systems. Nonetheless this might change for nanoparticulate systems as observed in a previous study of Pb(II) with a very small SiO2 particle (7.5 nm diameter).Besides, metal binding by those nanoparticles is surprisingly characterized by a heterogeneity which increases with the decrease of metal to particle ratio. Therefore, it is interesting to extend this study to investigate different trace metals and the influence of the nanoparticle size on the cation binding heterogeneity. Consequently, the Cd(II), Pb(II) and Zn(II) binding by two different sized SiO2 nanoparticles (Ludox LS30 and TM40) in aqueous dispersion was studied for a range of pH and ionic strength conditions, using the combination of the electroanalytical techniques Scanned Stripping ChronoPotentiometry and Absence of Gradients and Nernstian Equilibrium Stripping. The coupling of these techniques provides the free metal concentration in the bulk (AGNES) and information of the free and complex concentration at the electrode surface for each scanned deposition potential (SSCP). A recent mathematical treatment allows the reconstruction of a portion of the metal to ligand binding isotherm with the included heterogeneity information using the full SSCP wave analysis. In this work we observed that the Zn(II) binding is homogeneous, the Cd(II) is slightly heterogeneous and the Pb(II) is moderately heterogenous, while the results obtained with the 7.5 nm diameter nanoparticle are slightly more heterogeneous than those obtained with the one of 17 nm. These findings suggest that the Zn(II) binding is electrostatic in nature and for both the Cd(II) and Pb(II) there should be a significant chemical binding contribution.